Epitypification of the Linnaean name Lemna arrhiza (≡ Wolffia arrhiza), Araceae - Shiyan N.M. (Ukrainian Botanical Journal)
During our research on the genus Wolffia (Araceae) in Ukraine, we have investigated the typification status of the Linnaean name Lemna arrhiza (≡ Wolffia arrhiza). This name was typified twice, first using a “neotype” proposed by Landolt in 1994, and then a lectotype designated by Iamonico and Iberite in 2014. The “neotype” (a herbarium specimen preserved at FI) does not meet the requirements of Art. 9.8 of the International Code of Nomenclature for algae, fungi, and plants (ICN), because it is not part of the original material for Lemna arrhiza and, therefore, cannot be considered for the lectotypification purpose (Art. 9.3 and 9.4 of the ICN). On the other hand, the lectotype designated by Iamonico and Iberite (an illustration in the book by Micheli) fully complies with the provisions of the Code. However, Micheli’s illustration is demonstrably ambiguous and cannot be critically identified for purposes of the precise application of the name of Lemna arrhiza; therefore it was advisable to designate an epitype, following Art. 9.9 of ICN. The specimen from Micheli's Herbarium (barcode FI123857) is thus designated here as the epitype.